Pengaruh Insentif Terhadap Prestasi Kerja Karyawan Pada PT. Aplikanusa Lintasarta Jakarta Selatan - Dana Sandi Iskandar; Pandoyo (Klak Klik Inovasi Digital, 2020)
This research was conducted to determine how much influence the incentives have on the work performance of employees of PT. Aplikanusa Lintasarta South Jakarta. The research method uses correlation to know how big the influence of independent variables and the dependent variable. The sampling technique in this research were all employees of the saturated sample of 60 people, each respondent was given as many as 16 questions, using the Likert Scale. The results of data processing show that the incentive influence to employee job performance at PT. Aplikanusa Lintasarta South Jakarta at 19.36%, while the remaining 80.64% influenced by other factors not conducted in this research. Then, the relationship between the two variables X variables (incentives) and Y (job performance) of 0.44 or 44% which includes the criteria are.